Students’ Perceptions toward the Use of Podcast Video in Speaking Class - Lestari, Yunda; Devana , Trisilia; Rasheed, Abdul (Universitas PGRI Semarang, 2025)
This research aimed to find out students’ perception toward the use of podcast video in speaking class. This research was a case study. The participants were the second semester students of Speaking for Social Intercultural Class of English Department Study Program at Universitas Baturaja in the academic year of 2024/2025 with the total number of participants are 24 students. The data were collected through close-ended questionnaire and analyzed by percentage analysis and presenting data using tables. The result of the study showed that (1) Students had a good attitude toward the usage of podcast video in speaking class because podcast video is simple to utilize. Podcast video may help them learn to talk, and they are willing to use podcast video as an alternate method of learning to speak. Podcasts video can also motivate them since they attracted their interest. The podcast video's content and pronunciation of the native speaker could help them improve their talents. Furthermore, podcast video was easy to access; (2) The perception problems expressed by students regarding the use of podcast video in speaking class revealed that the length of the podcast is too long for them. Thus, they may get bored and lose their interest when watching a podcast video